The principal's office : a social history of the American school principal - Rousmaniere, Kate, 1958- (State University of New York Press, 2013)
In this book, the author explores the cultural, economic, and political pressures that have impacted school leadership over time and considers professionalization, the experiences of women and people of color, and progressive community initiatives. She discusses the intersections between the role of the school principal with larger movements for civil rights, parental and community activism, and education reform. The school principal emerges as a dynamic character in the center of the educational enterprise, ever maneuvering between multiple consituencies, responding to technical and bureaucratic demands, and enacting different leadership strategies. By focusing on the historic development of school leadership, this book provides insights into the possibilities of school improvement for contemporary school leaders and reformers. -- Description from back cover.